Suitability And Carrying Capacity Of The Silvo Mangrove Ecotourism Area In The Waters Of Kampung Bagan, Batam City, Riau Islands - Andi Zulfikar; mala kurnia; Febrianti Lestari (Universitas Andi Djemma Palopo, 2024)
Ecotourism is one effort that can be developed to preserve the mangrove ecosystem. This research aims to assess the suitability and carrying capacity of the Silvo mangrove ecosystem area so that it can be used as reference material in making mangrove ecosystem management policies. This research was carried out in November – January 2023 in Kampung Bagan, Batam City, Riau Islands Province. Data were analyzed using the Tourism Suitability Index (IKW) analysis matrix, spatial analysis using the Geographic Information System (GIS) approach followed by an assessment of Regional Carrying Capacity (DDK) to determine the maximum number of visitors that can be accommodated. The research results showed that IKW at the research location was in the very suitable category covering an area of 6.73 ha and 22.03 ha was in the suitable category so that the total IKW obtained was 28.76 ha. The length of the area that can be used for tracking activities is 1793.45 m and the carrying capacity of mangrove ecotourism is 287 people/day taking into account the travel time for each visitor (open 8 hours/day). Kampung Bagan as a whole is in the category suitable for being an ecotourism silvo area with tourist capacity in the good category and not exceeding the maximum allowed threshold. Therefore, the recommended policy decision is to create regulations related to mangrove ecosystem management